Efficiency and microbial community characteristics of strong alkali ASP flooding produced water treated by composite biofilm system - Wei, Dong; Zhang, Xinxin; Li, Chunying; Ma, Zhongting; Zhao, Min; Wei, Li (Frontiers in Microbiology, 2023)
Strong alkali alkali-surfactant-polymer (ASP) flooding produced water is a by-product of oil recovery, and it is a stable system composed of petroleum, polyacrylamide, surfactant, and inorganic salts. Efficient, green, and safe ASP produced water treatment technology is essential for oilfield exploitation and environmental protection. In this study, an anaerobic/anoxic/moving bed biofilm reactor with a microfiltration membrane was established and assessed for the real strong alkali ASP flooding produced water treatment. The results show that the average removal rates of COD, petroleum, suspended solids, polymers and surfactants in this process are 57%, 99%, 66%, 40% and 44%, respectively. GC-MS results show that most of the organic compounds such as alkanes and olefins in the strong alkali ASP produced water are degraded. Microfiltration membrane can significantly improve the efficiency and stability of sewage treatment system. Paracoccus (AN), Synergistaceae (ANO) and Trichococcus (MBBR) are the main microorganisms involved in the degradation of pollutants. This study reveals the potential and adaptability of composite biofilm system in treating the produced water of strong alkali ASP produced water.